DINAMIKA BATAS KEWENANGAN PENGAWASAN ANTARA OJK DAN BANK INDONESIA ATAS AKTIVITAS FINTECH DI SEKTOR PERBANKAN - Irwan Soeharlim; Hasnah Aziz; Muhammad Ruhunussa; Hikmat Ansori; Anharyanto (Berajah Journal, 2026)
The development of financial technology (fintech) in Indonesia has significantly transformed the financial services system and banking industry. Digital innovations such as electronic payments, peer-to-peer lending, open banking, digital banking, and embedded finance have created new challenges in terms of regulation and supervision. In practice, there are dynamics regarding the boundaries of authority between the Financial Services Authority (OJK) and Bank Indonesia (BI) as two state institutions responsible for regulation and supervision in the financial sector. This study aims to analyze the boundaries of supervisory authority between OJK and Bank Indonesia over fintech activities in the banking sector and their legal implications for legal certainty and consumer protection. This research uses normative legal research methods with statutory and conceptual approaches. The findings indicate that overlapping authorities still occur, particularly in digital payment services, digital banking, electronic payment systems, and the integration of fintech services with banking institutions. Such conditions potentially create regulatory disharmony and legal uncertainty. Therefore, stronger institutional coordination, regulatory harmonization, and the establishment of an integrated supervisory framework between OJK and Bank Indonesia are necessary to ensure effective, adaptive supervision and optimal legal protection for the public.